3-dimensional carbon Micro-electro Mechanical System (MEMS) electrode for potential dielectrophoretic hepatic cell patterning application / Wan Nurlina Wan Yahya - Wan Nurlina , Wan Yahya (2020)
The maintenance of liver tissue unique pattern remains a great challenge in the generation of functional engineered liver tissue in vitro. This thesis presents a carbon dielectrophoresis (DEP) based cell patterning for generating hepatic cell constructs, mimicking biological hepatic lobule. A new design of electrode named interdigitated radiating-strips electrode (IRSE) was simulated and optimized using COMSOL Multiphysics 4.2a. The simulation result proved that IRSE is capable to provide uniform distribution of electric field for generating three-dimensional (3D) DEP force. The use of carbon electrodes has been an alternative to traditional metal electrodes and insulator structures for DEP applications since more advantages offered. The proposed lab-on-a chip (LOC) device composed of three layers and feature 3D carbon IRSE which was fabricated using a carbon micro-electro-mechanical system (CMEMS) technique. The electrical characterization result of the fabricated carbon electrode shows that the average electrode resistivity is 10.36 ± 1.19 × 10-4 Ω·m, which low enough to generate an electric field for DEP application using 10 of volts. A proof-of-concept experiment using an interdigitated circular post electrode was conducted to confirm the functionality of the fabricated LOC device. Results show that with the presence of a 15 V voltage input, this carbon structure was capable of manipulating polystyrene microbeads through negative DEP and positive-DEP in a range of frequency. In the guise of IRSE, both two dimensional (2D) and 3D structures were fabricated and 10 µm polystyrene microbeads were used as a model to demonstrate dielectrophoretic cell patterning. Under 15 V of AC signal and 50 MHz of frequency in 1 minute, 3D IRSE shows a 67% increase in trapping efficiency of pDEP microbeads as compared to the 2D IRSE. This result suggests that the 3D carbon electrode has the capacity to generate strong electric field gradients over the microchannel which is in line with the simulation result. Certainly, this CMEMS technique can be utilized to engineer a 3D carbon electrode for DEP application and has a great potential to be applied for 3D hepatic cell patterning. Future applications of the fabricated LOC device include artificial organs for integration in the human-on-a-chip system, drug development, and toxicity screening, as well as the modeling of patient specific liver illness.